1999
DOI: 10.1530/eje.0.1400069
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid polypeptide/amylin messenger RNA and protein expression in human insulinomas in relation to amyloid formation

Abstract: Objective: Islet amyloid polypeptide (IAPP), also named amylin, is the predominant protein component of amyloid deposits in human islet b cell tumours of the pancreas (insulinomas). IAPP is co-produced with insulin by islet b cells. We investigated IAPP expression in relation to insulin expression and to amyloid formation in eleven insulinomas. Design and methods: RNA and protein extracts were prepared from the same pieces of tumour tissue, and from specimens of two normal human pancreata. IAPP and insulin mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…Amyloid deposits have been demonstrated in more than 50% of insulinomas, but not to the extent present in our patient's tumor (12,13). The major component of the amyloid of an insulinoma is a 37-amino acid polypeptide known as islet amyloid polypeptide or amylin.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Amyloid deposits have been demonstrated in more than 50% of insulinomas, but not to the extent present in our patient's tumor (12,13). The major component of the amyloid of an insulinoma is a 37-amino acid polypeptide known as islet amyloid polypeptide or amylin.…”
Section: Discussioncontrasting
confidence: 55%
“…The major component of the amyloid of an insulinoma is a 37-amino acid polypeptide known as islet amyloid polypeptide or amylin. Islet amyloid polypeptide has been observed within the tumor cells and the stroma surrounding the islet cells of patients with an insulinoma as well as in the stroma surrounding the islet cells of patients with insulinomas and patients with type II diabetes mellitus (12,13). Overexpression of islet amyloid polypeptide, with aberrant processing and secretion by abnormal ␤-cells of the insulinoma, is postulated to be the cause of amyloidogenesis (13).…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by the findings that 1) islet amyloid was detected only in hIAPP transgenic mice from line No18, with higher plasma IAPP concentrations than mice from line No14; 2) islet amyloid developed mainly in homozygous transgenic mice [19]; 3) among the ob/ob mice, there was a positive correlation between the degree of amyloid deposition (Amyloid Index at t3) and the plasma IAPP concentrations at t1 and t2; 4) hIAPP amyloid develops in approximately 50 % of human beta-cell tumours (insulinomas), which overproduce IAPP in addition to insulin [24], i. e. in patients who are hypoglycaemic rather than hyperglycaemic. Amyloid is detected particularly in those insulinomas which have a high IAPP content [25]. Although these data strongly indicate that high hIAPP production rather than hyperglycaemia as such is an amyloidogenic factor, it cannot be excluded that the diabetic state might enhance islet amyloid deposition.…”
Section: Discussionmentioning
confidence: 85%
“…It has been suggested that in those cases IAPP is probably retained in tumour cells and not secreted (16). In addition, although IAPP mRNA has been found in the gastrointestinal tract, dorsal root ganglia, and lung (17), circulating IAPP levels were not increased in patients with gastrointestinal tumours, where the peptide was detected in the respective tissues using immunohistochemistry (14).…”
Section: Discussionmentioning
confidence: 99%